How CEO/Founders' Social and Political Expression Impacts Gen Z's Brand Loyalty: A Comparative Analysis of Starbucks, Ben & Jerry’s, and Spotify - Boldrini,Aurora; Paolucci,Elena; Schmidt,Simon (LBMG Strategic Brand Management - Masters Paper Series, 2025)
Purpose: The study examines how CEOs' and founders' social and political declarations influence Generation Z's conditional brand loyalty in an era in which personal and corporate identity are more intertwined than ever. Focusing on how leaders' public stands on controversial topics—in particular the Israel-Palestine conflict—determine consumer trust, the research aims to establish strategies for dealing with identity spillover and authenticity threats in the context of Brand Activism. Methodology approach: Using a comparative multi-case study approach, the research investigates three global brands: Ben & Jerry's, Starbucks, and Spotify. Social media posting sentiment analysis, financial statements, and a consumer survey assessing pre- and post-exposure value congruence, purchase intention, and Net Promoter Score for each brand or CEO's political stance yielded the data. The Vision-Culture-Image (VCI) model further guided the investigation to diagnose mismatched alignment in leadership vision, internal culture, and public image. Findings: Research indicates that authenticity, consistency, and identity congruence are the determinants for sustaining Gen Z consumers' loyalty. Ben & Jerry's authenticity supported trust and advocacy despite the controversy, while Starbucks and Spotify experienced backlash due to perceived value misalignment and communication failures. Across cases, brand activism was a double-edged sword—enhancing emotional engagement for some audiences while provoking reputational volatility for others. Originality/value: This research contributes to the literature on CEO and Brand Activism by illustrating how leadership expression shapes consumer trust and conditional loyalty in polarised socio-political contexts. The proposed framework offers actionable insights for decision
Keywords: Brand Activism; CEO Activism; Gen Z; Brand Loyalty; Corporate Identity; Brand Equity